Everyday challenges following hospital discharge. A multi‐method study identifying and describing areas of concern for patients during the first month after colorectal cancer surgery - Jenny Jakobsson; Christine Kumlien (Wiley, 2023)
Abstract Aim Identify and describe areas of concern focusing on day‐to‐day variations during the first month after surgery for patients recovering from colorectal cancer surgery. Design A multi‐method design was applied using diaries and interviews. Method Data was collected using semi‐structured diaries kept 1 month after surgery by seven patients recovering from colorectal cancer surgery. Also, face‐to‐face interviews were conducted 1 month after surgery. Data from the diaries constituted a framework for the following directed content analysis of interviews. Findings Low levels of pain were experienced but caused reduced mobility and tiredness. Practical matters in daily living were restricted, while social life could be hampered by a frequent need to defecate. Appetite and consequently the ability to eat and drink was the most prominent concern, due to changes in taste and ability to tolerate food. Worries were mainly related to changes in bowel movements. No Patient or Public Contribution.